The Relations Of Design And The Role Of It Making The Idea For Fashion Design: فرات جمال العتابي (Al-Academy, 2021)
Any design subject to a set of forces contributing to the establishment of relations working to strengthen the internal elements of the design; any imbalance in these elements can make a fragmented and weak design, thus preventing it from achieving the goal or performance. Poor performance can be attributed to various factors: the extent and function of the elements and principles in the design, realization of the idea, especially in fashion design.Moreover, there are many aspects of a design that go into achieving the realization of the designer’s idea. The design utilizes a lot of stimulants by drawing attention to its design, which is consistent with the need for psychological and material individuals. In this research, we will analyze the most important elements and relations that contribute to the idea, and then provide an analysis of the technical and functional aspects of the design